Eccrine Spiradenoma Arising from the Breast Skin - Mark A. Benedict; Ugur Ozerdem (Case Reports in Pathology)
Eccrine spiradenomas are uncommon, benign lesions, which are thought to originate from the eccrine sweat glands. They are common in young adults and are without a sex predilection. Here we report a case of eccrine spiradenoma of the breast skin in a 39-year-old woman who presented with a breast nodule for 10 years. It is crucial to take eccrine spiradenoma into consideration in superficial, well-circumscribed, breast skin/subcutaneous lesions. It is useful to recognize the two-cell populations constituting this tumor: small, dark, basaloid cells with hyperchromatic nuclei, which are immunoreactive for P63 and calponin, and larger cells with a pale nucleus, often near the center of the cluster (inner cells), which are immunoreactive for CK7 and CD117 (C-kit).